The Effect of Competency, Organizational Culture and Compensation on PPPK Employee Performance using Motivation as Intervening Variable: The Case of Land Office of South Sumatera, Indonesia - Lesmana, Redy; Asiati, Diah Isnaini; Yamaly, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to determine the effect of competence, organizational culture, and compensation on the performance of PPPK, with motivation serving as an intervening variable, at the Land Office in South Sumatra. This type of research is associative. The variables used by the researcher are competence, organizational culture, compensation, motivation, and performance, which are developed into 11 indicators. The population of this study consisted of all 149 PPPK employees at the Land Office in South Sumatra, and the research sample comprised 110 employees, selected using a Simple Random Sampling technique. The data used in this study were primary data collected using a questionnaire. The data analysis technique used was Structural Equation Modeling (SEM). The results of this study show that: 1) Competence has a significant effect on the motivation of PPPK at the Land Office in South Sumatra. 2) Organizational culture has a significant effect on the motivation of PPPK at the Land Office in South Sumatra. 3) Compensation has a significant effect on the motivation of PPPK at the Land Office in South Sumatra. 4) Competence has a significant effect on the performance of PPPK at the Land Office in South Sumatra. 5) Organizational culture has a significant effect on the performance of PPPK at the Land Office in South Sumatra. 6) Compensation has an insignificant effect on the performance of PPPK at the Land Office in South Sumatra. 7) Motivation has a significant effect on the performance of PPPK at the Land Office in South Sumatra. Motivation strengthens the effect of competence, organizational culture, and compensation on the performance of PPPK at the Land Office in South Sumatra.